First insight into the faecal microbiota of the high Arctic muskoxen (Ovibos moschatus). Issue 7 (29th April 2016) - Salgado-Flores, Alejandro; Bockwoldt, Mathias; Hagen, Live H.; Pope, Phillip B.; Sundset, Monica A.
Abstract : The faecal microbiota of muskoxen ( n =3) pasturing on Ryøya (69° 33′ N 18° 43′ E), Norway, in late September was characterized using high-throughput sequencing of partial 16S rRNA gene regions. A total of 16 209 high-quality sequence reads from bacterial domains and 19 462 from archaea were generated. Preliminary taxonomic classifications of 806 bacterial operational taxonomic units (OTUs) resulted in 53.7–59.3 % of the total sequences being without designations beyond the family level. Firmicutes (70.7–81.1 % of the total sequences) and Bacteroidetes (16.8–25.3 %) constituted the two major bacterial phyla, with uncharacterized members within the family Ruminococcaceae (28.9–40.9 %) as the major phylotype. Multiple-library comparisons between muskoxen and other ruminants indicated a higher similarity for muskoxen faeces and reindeer caecum ( P >0.05) and some samples from cattle faeces. The archaeal sequences clustered into 37 OTUs, with dominating phylotypes affiliated to the methane-producing genus Methanobrevibacter (80–92 % of the total sequences). UniFrac analysis demonstrated heterogeneity between muskoxen archaeal libraries and those from reindeer and roe deer ( P =1.0e-02, Bonferroni corrected), but not with foregut fermenters. The high proportion of cellulose-degrading Ruminococcus -affiliated bacteria agrees with the ingestion of a highly fibrous diet. Further experiments are required to elucidate the role played by these novel bacteria in the digestion of this fibrous Artic diet eaten by muskoxen.